Multiwavelength UV-Metric and pH-Metric Determination of the Dissociation Constants of the Hypoxia-inducible Factor Prolylhydroxylase Inhibitor Roxadustat - Meloun, Milan; Pilařová, Lucie; Javůrek, Milan; Pekárek, Tomáš (My University, 2018)
UV-VIS spectra, molar absorption coefficients and protonation equilibriaRoxadustat is an orally bioavailable, hypoxiainducible factor prolyl hydroxylase inhibitor with potential anti-anemic activity. It is one of the Active Pharmacenutical Ingredients possessing acidic/basic functionalities their ionization state is controlled by solution pH and acid dissociation constants. Nonlinear regression of the pH-spectra with programs REACTLAB and SQUAD84 and of the pH-titration curve with ESAB determined four multiple consecutive dissociation constants with the protonation scheme. A sparingly soluble neutral molecule LH3 of Roxadustat was dissociated to the soluble anions LH2-, LH2- and L3- or protonated to the cation LH4+ in an aqueous medium. The graph of molar absorption coefficients of variously protonated species according to wavelength shows that the spectra of two anions LH2- and LH2-are nearly the same in colour. The Roxadustat spectrum exhibited five sharp isosbestic points related to the LH2-/L3- equilibrium. Four consecutive thermodynamic dissociation constants were estimated using UV-metric data pKTa1 = 3.60(04), pKTa2 = 5.62(14), pKTa3 = 7.66(16), pKTa4 = 9.08(02) at 25°C and pKTa1 = 3.60(04), pKTa2 = 5.73(10), pKTa3 = 7.52(10), pKTa4 = 8.99(02) at 37°C and using pH-metric data pKTa1 = 4.33(09), pKTa2 = 6.57(11), pKTa3 = 8.88(05), pKTa4 = 9.03(04) at 25°C and pKTa1 = 4.25(09), pKTa2 = 6.49(10), pKTa3 = 8.80(06), pKTa4 = 9.00(05) at 37°C The positive values of the enthalpy ΔH0 showed that the dissociation process is endothermic and the positive values of the Gibbs free energy ΔG0 at 25°C indicated that the dissociation process was not spontaneous, which also was confirmed by a negative value of the entropy ΔS0. Four macro-dissociation constants of Roxadustat and six protonation locations were predicted by MARVIN.
Vícenásobné spektrální UV-metrické a pH-metrické stanovení disociační konstanty inhibitoru prolylhydroxylázy indukovatelného hypoxií Roxadustatu
Keywords: Dissociation constants; Roxadustat; spectrophotometric titration; pH-titration; REACTLAB; SQUAD84; ESAB; Disociační konstanty; Roxadustat; spektrofotometrická titrace; titrace pH; REACTLAB; SQUAD84; ESAB